Lower Firmicutes abundance in gut microbiota associated with amyloid-β positivity in older adults in Japan as assessed by positron emission tomography - Narumi Kojima; Yosuke Osuka; Hiroyuki Sasai; Shoji Shinkai; Kenji Ishii; Noriyuki Kohda; Yodai Kobayashi; Hunkyung Kim (PLoS ONE, 2025)
Background Alzheimer’s disease, marked by amyloid-β accumulation, is a leading cause of dementia. Gut microbiota may influence its development by affecting inflammation or amyloid-β metabolism. However, this association is not well studied in older adults in Japan, whose characteristic diet may uniquely impact gut bacteria. Objective To determine the association between the gut microbiota and positron emission tomography (PET)-determined brain amyloid-β positivity in community-dwelling older adults in Japan. Methods This cross-sectional study investigated 136 participants aged 68–86 years from Tokyo. Brain amyloid-β was assessed using PET imaging, and gut microbiota were analyzed from fecal samples using 16S rRNA gene sequencing processed with the QIIME2 pipeline. Taxonomic composition was evaluated at both the phylum and genus levels; participants were classified into above- and below-median groups based on the relative abundance of each taxon. Binomial logistic regression adjusted for age, sex, and antibiotic use was conducted to examine the association between bacterial abundance and PET positivity. For genus-level analyses, p-values were further corrected for multiple comparisons. In addition, α diversity (Shannon, Simpson, Observed OTUs) and β diversity (PCoA based on unweighted UniFrac distances, PERMANOVA) were compared between PET-positive and PET-negative groups. Results Of the 136 participants, 34.6% were PET-positive for amyloid-β. Firmicutes showed a significant difference: 26.4% PET-positive in the above-median group vs. 42.6% in the below-median group (p for χ² = 0.047). The binomial logistic regression analysis showed that lower Firmicutes abundance was significantly associated with an increased odds of PET positivity (odds ratio and confidence interval: 2.15 [1.03, 4.52]). At the genus level, no taxon remained significant after correction for multiple comparisons. No significant differences were observed in α or β diversity indices between groups. Conclusion A lower abundance of Firmicutes may be associated with amyloid-β accumulation in the brain, linking the gut microbiota to Alzheimer’s disease.